2014
DOI: 10.1016/j.bbmt.2014.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Double Umbilical Cord Blood Transplantation after Novel Myeloablative Conditioning Using a Regimen of Fludarabine, Busulfan, and Total Lymphoid Irradiation

Abstract: We conducted a pilot study evaluating double umbilical cord blood transplantation (dCBT) after myeloablative (MA) conditioning with Fludarabine/Busulfan 3.2mg/kg IV × 4, followed by Total Lymphoid Irradiation at 400cGy (FluBu4/TLI) for any indicated hematological disorder without a suitable donor. Twenty patients with predominantly high-risk disease underwent dCBT according to protocol. The regimen was well tolerated, with mucositis as the primary observed toxicity (n=19). The cumulative incidence of neutrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…The myeloablative regimen of thiotepa, busulfan, fludarabine, and anti-thymocyte globulin is also associated with a low early TRM of 20% at 180 days, but this regimen has been studied in a considerably younger population of patients receiving single UCB transplantation 7, 24, 25 . At one and three years after TBI, fludarabine, and thiotepa, TRM increased to 24% and 30%, respectively, similar to later TRM rates observed with other myeloablative regimens 5, 9, 10, 24, 25 . The encouraging low early TRM with thiotepa, TBI, and fludarabine may reflect decreased regimen-related toxicity, while the rise in later TRM may be influenced by other factors such as graft versus host disease and immune reconstitution.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The myeloablative regimen of thiotepa, busulfan, fludarabine, and anti-thymocyte globulin is also associated with a low early TRM of 20% at 180 days, but this regimen has been studied in a considerably younger population of patients receiving single UCB transplantation 7, 24, 25 . At one and three years after TBI, fludarabine, and thiotepa, TRM increased to 24% and 30%, respectively, similar to later TRM rates observed with other myeloablative regimens 5, 9, 10, 24, 25 . The encouraging low early TRM with thiotepa, TBI, and fludarabine may reflect decreased regimen-related toxicity, while the rise in later TRM may be influenced by other factors such as graft versus host disease and immune reconstitution.…”
Section: Discussionsupporting
confidence: 66%
“…This improved rate of neutrophil engraftment may be related to the described immunosuppressive property of thiotepa 14 . Furthermore, neutrophil engraftment with the thiotepa, TBI, and fludarabine regimen was comparable to engraftment rates ranging from 86% to 94% in recent reports of other myeloablative conditioning regimens for adult UCB transplantation 5, 9, 24, 25 .…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Conditioning regimens were either the widely accepted Minnesota protocol, which consisted of TBI/cyclophosphamide/ fludarabine or thiotepa/busulphan/fludarabine (TBF). In this study, 2 years LFS was similar between double-unit cord and single-unit cord if the new TBF protocol was chosen [75,77]. In a prospective multicenter trial, which included 56 acute leukemia and myelodysplasia patients transplanted with double-unit cord, 3 years disease-free survival was 50% and TRM was 39% [76].…”
Section: Umbilical Cord Bloodmentioning
confidence: 88%
“…In the setting of CBT, the FluBu regimen has not been widely accepted because of a high rate of engraftment failure reported in several studies [4,11]. Recently, some investigators reported successful engraftment of CB units by adding low doses of total-body irradiation (TBI), thiotepa, or antithymocyte globulin (ATG) to the FluBu4 regimen [12][13][14][15], suggesting that additional immunosuppressive agents would be crucial to overcome rejection. Our retrospective analysis of various FluBu regimens in CBT confirmed that adding melphalan (Mel), a DNA alkylating agent with both immunosuppressive and myeloablative properties [16,17], to FluBu regimens has potential to achieve successful engraftment without increasing NRM [15].…”
Section: Introductionmentioning
confidence: 99%